Kemampuan Berpikir Kreatif dalam Menyelesaikan Soal Model PISA Konten Space and Shape Ditinjau dari Kemandirian Belajar - Aisyah Najma Kamilah; Ismail Ismail (MATHEdunesa, 2026)
Creative thinking ability is an essential skill for students to face the challenges of the 21st century. This ability enables students to find various solutions to contextual problems, such as those presented in PISA-type questions. However, Indonesian students’ creative thinking skills are still considered low based on international assessments like PISA. One contributing factor is the varying levels of students' self-regulated learning. This study aimed to describe students' creative thinking abilities in solving PISA-type questions in the Space and Shape content area, viewed from self-regulated learning. A qualitative descriptive approach was used, with three eighth-grade students from SMP Negeri 2 Surabaya (academic year 2024/2025) as subjects, selected based on their high, moderate, and low levels of self-regulated learning. Data collection involved a mathematics proficiency test, a self-regulated learning questionnaire, a PISA-type problem-solving test in the Space and Shape domain, and semi-structured interviews. Creative thinking indicators referred to Guilford and Torrance’s theory: fluency, flexibility, originality, and elaboration. Results showed that the student with high self-regulated learning demonstrated strong creative thinking across all four indicators. The student with moderate self-regulated learning showed relatively high ability in fluency and elaboration, and moderate performance in flexibility and originality. Conversely, the student with low self-regulated learning tended to show weak performance across all indicators. These findings indicate a positive relationship between the level of self-regulated learning and the quality of students’ creative thinking in solving contextual PISA-type problems